Geniposide Combined With Notoginsenoside R1 Attenuates Inflammation and Apoptosis in Atherosclerosis via the AMPK/mTOR/Nrf2 Signaling Pathway - Liu, Xiaoyu; Xu, Yuling; Cheng, Saibo; Zhou, Xinghong; Zhou, Fenghua; He, Peikun; Hu, Fang; Zhang, Lifang; Chen, Yuyao; Jia, Yuhua (Frontiers in Pharmacology, 2021)
Inflammation and apoptosis of vascular endothelial cells play a key role in the occurrence and development of atherosclerosis (AS), and the AMPK/mTOR/Nrf2 signaling pathway plays an important role in alleviating the symptoms of AS. Geniposide combined with notoginsenoside R1 (GN combination) is a patented supplement for the prevention and treatment of AS. It has been proven to improve blood lipid levels and inhibit the formation of AS plaques; however, it is still unclear whether GN combination can inhibit inflammation and apoptosis in AS by regulating the AMPK/mTOR/Nrf2 signaling pathway and its downstream signals. Our results confirmed that the GN combination could improve blood lipid levels and plaque formation in ApoE-/- mice fed with a high-fat diet (HFD), inhibit the secretion of serum inflammatory factors and oxidative stress factors. It also decreased the expression of pyrin domain containing protein 3 (NLRP3) inflammasome-related protein and Bax/Bcl2/caspase-3 pathway-related proteins. At the same time, the GN combination could also inhibit the H2O2-induced inflammatory response and apoptosis of human umbilical vein endothelial cells (HUVECs), which is mainly related to the activation of the AMPK/mTOR pathway by GN combination, which in turn induces the activation of Nrf2/HO-1 signal. In addition, the above phenomenon could be significantly reversed by dorsomorphin. Therefore, our experiments proved for the first time that the GN combination can effectively inhibit AS inflammation and apoptosis by activating the the AMPK/mTOR/Nrf2 signaling pathway to inhibit the NLRP3 inflammasome and Bax/Bcl2/caspase-3 pathway.